Enduring Transience: The illusion of ‘Temporary Finality’ in Construction Adjudication Decisions (Strathmore Law Review, 2025)
Construction Adjudication is not adequately regulated in Kenya. Despite its benefits in quickly resolving disputes, it is poorly understood and not widely used except when mandated by a contract or on an ad hoc basis. There are efforts to usher in statutory adjudication, as prescribed in the National ADR policy, through the enactment of a proposed Construction Adjudication Bill to strengthen its legal framework. Indeed, other jurisdictions have utilised Construction Adjudication to streamline dispute resolution and improve cash flow in construction contracts. To achieve this, a statutory adjudication regime rides on unique features that prioritise speed over due process as its decisions are temporarily binding until contested in a final forum. However, these decisions are not always temporary. Some events and circumstances can make them final and binding, potentially leading to unfair and unjust outcomes that may infringe the constitutionally guaranteed right of access to justice. The paper urges caution while establishing a statutory adjudication regime to ensure robust safeguards are incorporated to mitigate these risks. It also encourages legislation that is customised to the specific and unique attributes of the Kenyan construction industry.